Toward Adaptive Load Shedding Remedial Action Schemes in Modern Electrical Power Systems - M. A. Toro-Mendoza; Juan Segundo-Ramirez; Aaron Esparza-Gurrola; Nancy Visairo-Cruz; C. Alberto NuNez Guitierrez; C. Perez-Negron (IEEE Access, 2023)
Modern power grids are becoming more stressed, more complex, and beginning to have a significant integration of energy sources based on power electronics devices, which significantly changes the dynamics of power grids affecting the design and operation of Remedial Action Schemes such as UVLS and UFLS, where the conventional operation philosophy of these schemes is based in operating parameters such as thresholds, amount, and location of the load shedding fixed regardless of the event. Therefore, they are not adaptable to the various conditions of the modern power grids, causing their misoperation. In recent years, a wide variety of adaptive schemes around the world have been proposed as a solid solution with good performance, since its main characteristic is its ability to consider the magnitude of the event in its load shedding, turning them into more selective and with flexibility in their operating parameters. The aim of this article is to review the development of adaptive schemes in UVLS and UFLS over the years, identifying how to approach the design of such adaptable schemes, which operating parameters tend to give them greater flexibility and which have been less explored. Then broken down the methods used to give flexibility to the operating parameters of UVLS and UFLS, and also that other devices such as FACTS and ESS can enhance its operation, with the aim of provide a broad vision of how to give them flexibility to these parameters and which of them are identified as an opportunity to improve the performance of the adaptive schemes. Finally, the review includes some RAS with adaptive approach implemented in real systems which some of them includes load shedding, to show how these schemes have reconfigured their design and operation by giving flexibility to some operating parameters, it is possible to show the need of modern power grids to have adaptive RAS.